Comparative leaf micromorphological characters of the Nigerian species of rauvolfia linn (apocynaceae) (2003)
Leaf micromophological characters of Rauvolfia Linn. (Apocynaceae) have been studied and compared. The leaf is usually glabrous and hypostomatic. Stomatal type is mostly paracytic but epidermal cell shape is either polygonal or irregular while epidermal cell number is lower on the abaxial surface. Mean stomatal size varies from 1.40.µm x 0.60µm in R. macrophylla to 2.30µm x 0.60µm in R. vomitoria and mean cell wall thickness is either identical on both surfaces in R. macrophylla and R. caffra or dissimilar on either surface in other species. Other features that show variation are anticlinal wall pattern, stomatal and cell inclusions. Using these micro-characters, the species can be recognised even when the leaves are fragmentary. Rauvolfia has therapeutic properties for the treatment of neuropsychiatric disorder and it can be used as aphrodisiac and genital excitant.